Complementary and Alternative Medicine Use Among Women Receiving Chemotherapy for Ovarian Cancer in 2 Patient Populations. Issue 3 (1st April 2011) - Helpman, Limor; Ferguson, Sarah E.; Mackean, Melanie; Rana, Amira; Le, Lisa; Atkinson, Morven A.; Rogerson, Andrew; Mackay, Helen
Abstract : Objective: The authors evaluated attitudes toward complementary and alternative medicine (CAM) use in 2 populations of women receiving chemotherapy for epithelial ovarian cancer (EOC). Methods: Women with EOC currently being treated with chemotherapy at 2 tertiary cancer centers, in Canada and the United Kingdom, completed a self-administered questionnaire on attitudes and perceptions of CAM and types of CAM used within the previous month. Results: One hundred ninety-two patients (94 from Canada, 98 from United Kingdom) completed the questionnaire. Overall, 85 women (44%) were identified as CAM users. Complementary and alternative medicine use was more common among Canadian women (52%) compared with women from the United Kingdom (37%), P = 0.02. Participants used 71 different types of CAM, the majority (61%) taking multiple CAM. The frequency of CAM use was the same in primary compared with recurrent disease. Eighty-nine percent of CAM users considered it important for their oncologist to be aware of CAM use. Canadian women, however, were less likely to inform their physician (Canada: 50%; United Kingdom: 81%), P = 0.02. Motivations for CAM use were the same in both populations including assist healing (60%), boost the immune system (57%), improve quality of life (48%), and relieve symptoms (45%). Thirteen percent thought CAM could cure cancer, whereas 17% thought it would prevent recurrence. Conclusions: Complementary and alternative medicine use is common in women receiving chemotherapy for EOC. Increasingly, interactions between CAM and prescribed medication are being identified. Oncologists should be aware and actively inquire about CAM use. Although patterns of CAM use differed, the motivation for starting CAM was similar, highlighting the need to address supportive care in all patients.